Prevalence and associated factors for asthma in adults in Quito: a cross-sectional study (Colombia Medica, 2022)
BackgroundAlthough several epidemiological studies of asthma have been carried out in Ecuador in the last two decades, none of these has estimated the prevalence of asthma in adult populations.ObjectiveTo estimate the prevalence of asthma symptoms in adults in the city of Quito and to identify possible associated factors.MethodsA cross-sectional study was carried out on subjects older than 18 years residing in the Metropolitan District of Quito. The Global Asthma Network (GAN) questionnaire was applied to collect information on asthma symptoms and sociodemographic and lifestyle data. Bivariate and multivariate analyses with logistic regression were used to identify asthma-associated factors.Results2,476 subjects answered the questionnaire (80.9% women, mean age 40 years). The prevalence of wheezing in the last 12 months, asthma ever, and asthma diagnosed by a doctor were 6.3%, 1.9% and 1.6%, respectively. The prevalence of rhinitis and eczema was 13.7% and 5.5%. The presence of mould at home (OR: 2.13; 95% CI: 1.48-3.06; p